Laboratory-based diagnosis of scabies: a review of the current status. (25th March 2021) - Siddig, Emmanuel Edwar; Hay, Roderick
Abstract: Scabies is a neglected tropical disease (NTD) of the skin that is caused by the mite Sarcoptes scabiei . It is considered to be an important public health problem in many regions. The disease is at its most prevalent in low-resource countries where there are overcrowded living conditions coupled with poor hygiene. In some regions, mass drug administration using ivermectin is a key population-based approach to the control of scabies. Before starting a patient on specific treatment, confirming the diagnosis by accurate and rapid identification of the organism is critical. Different laboratory-based techniques for scabies have been developed in the last few decades. These include direct microscopy and histopathology. More recently, serological testing, dermoscopy and different molecular techniques have been developed as diagnostic methods for scabies. To date, none of these, apart from microscopy and dermoscopy, has been translated into routine clinical laboratory practice. A simple point-of-care or laboratory test would provide a rapid and confirmed diagnosis and early institution of effective treatment. In this review we present an update on the laboratory techniques currently in use for the identification of scabies.